EFEKTIVITAS PEMBELAJARAN DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK PADA MATERI KUBUS DAN BALOK DI SMPN - Massita, Massita; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to find the effectiveness of the realistic mathematics education approach in learning cube and rectangular parallelepiped materials at SMP N 7 Pontianak. The method used in this research is pre-experimental method with one-shot case study design. The aspects that be used to determine the effectiveness of the realistic mathematics education approach are student?s activity, teacher?s realization lesson plan, student?s responses, and student?s learning outcomes. The used data collection technique are observation and indirect communication techniques. The used data collection tools are the student?s learning outcomes test, which contains 4 essay questions, the observation sheet of student?s activity, the observation sheet of teacher?s realization lesson plan, and student?s responses questionnaire. The research data were analyzed descriptively. The results that obtained are student?s activity is classified as active, teacher?s realization lesson plan is classified as very good, student?s learning completeness classically is not fulfilled ( of 34 students are not complete), and positive responses by the student. So the learning using the realistic mathematics education approach in learning cube and rectangular parallelepiped materials at SMP N 7 Pontianak is not effective. Keywords :  effectiveness of teaching and learning, the realistic mathematics education approach in learning, cube and rectangular parallelepiped materials